Traditional nutrition of Indigenous Peoples in the Arctic zone of Western Siberia : challenges and impact on food security and health - Bogdanova, Elena; Lobanov, Andrey; Andronov, Sergei; Popov, Andrei; Kochkin, Ruslan; Asztalos Morell, Ildikó (2020)
The chapter presents traditional nutrition as a part of the traditional culture of the nomadic Indigenous population in the Arctic zone of Western Siberia. Traditional nutrition effectively prevents health problems and enables people to adapt to the harsh climate conditions of the High North. This chapter analyses the implementation of Russian national policies on traditional reindeer herding in this region that is affected by issues of food security and food sovereignty. Export trends of traditional products have decreased local Indigenous Peoples’ access to venison, negatively impacting their health.